Use of Abbreviations in Medical Consent Forms at X Hospital in Indonesia: A Descriptive Analysis - Gama Bagus Kuntoadi; Ima Rusdiana; Miftah Parid Firmansyah (International Journal of Health and Medicine, 2026)
This study identified the use of abbreviations in Medical Treatment Consent Forms (SPTK) at X Hospital Indonesia. A quantitative cross-sectional descriptive approach was applied to 76 SPTKs in September 2024, and questionnaires were administered to 30 patient-responsible physicians (DPJP). The results showed that 75% of SPTKs contained abbreviations, even though 97% of respondents understood the risk of miscommunication to patient safety. The state of the art includes accreditation standards that prohibit the use of abbreviations in informed consent, with global orthopedic studies reporting a decrease from 54% to 22% after educational interventions, as well as Indonesian regulations, namely Peraturan Mentri Kesehatan (Permenkes) Republik Indonesia No. 24/2022, which emphasizes that medical records must be complete. The novelty lies in the first empirical analysis in Indonesian hospitals to reveal the disparity between high physician knowledge and low documentation compliance, contributing to the development of evidence-based monitoring for patient safety. These findings support recommendations for daily review of SPTK, ongoing socialization, and integration of digital checklists to reduce medical errors.